(3QSGdg hGVY jO Gdjefi Ydi GdjSQis - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eGdc QbGH GdCee CeG HYO ajbhd bO hbYJ eHGMKI Hjfi hHjf HYV GdaVdGA abGd hQO ai UMjM eSde Cfg Udi Gddg Ydjg hSde (B" (3hVY jOg Gdejfi Ydi GdjSQi (B" s
(3BNQgG (B:s
(3aEfgeG EPG JYGQVG JSGbWG aGdJNjjQ hGdEHGMI HgeG JQGHWkG hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs